The Existence of Melayu Riau Gambus Amid the Millennial Generation in Pekanbaru City - Laila Fitriah; Muhammad Jazuli; Wadiyo Wadiyo; Eko Sugiarto (Universitas Negeri Semarang, 2022)
Looking at the current phenomenon, the influence of foreign culture in millennial period is increasing significantly. In this era, entertainment exposure from social media is rising rapidly which creates direct and indirect marginalized effect on traditional art. Melayu Riau Gambus is one of Melayu society traditional arts characteristic which its development is quite exist among any other traditional arts in Pekanbaru city. This condition is due to the active young generation who constantly creates innovation to gambus art. this research aims to discuss how is the existence of gambus art and what are the innovations done by gambus artist in order to keep its existence and interest of millennial generation. This research used qualitative method, the data are collected by observation, in-depth interview with gambus artist and its aesthete, and documentation that become the supporting data to this writing. Descriptive qualitative analysis is used by the application of social change and art communication theory. The result of this research shows that the innovation of gambus melayu has increasing through its musician regeneration, function development, the changing of show rapporteur, the utilization of digital technology that appeals the millennial generation to strengthen, study and promote melayu riau gambus in international level.